Faktor Penentu Kinerja Usaha Kecil Menengah (UKM) di Kabupaten Barru - Khaerunnisa Khaerunnisa; Jusni Jusni; Maat Pono (Hasanuddin Journal of Business Strategy, 2019)
This study aims to determine the Determinants of the Performance of Small and Medium Enterprises (SMEs) in Barru Regency. The method used in this study is a quantitative approach and the type of research conducted is survey research. The population used is Small and Medium Enterprises in the manufacturing industry sector in Barru Regency, which is 1672 business units. The number of samples is 94 small and medium enterprises. The data sources used are primary data and secondary data. Analysis of the data used is multiple linear regression analysis. The results of this study indicate that the aspects of finance, environment, marketing, human resources, entrepreneurial ability and economic aspects have a positive and significant effect on the performance of small and medium enterprises in Barru Regency. The greater the equity, loan capital, the level of profits and capital accumulation, the greater the performance of small and medium enterprises. The better the technology and quality control, the availability of business places, government policies, seasons and infrastructure, the better the performance of small and medium enterprises. The more market demand, the better competing pricing, promotion, distribution channels and marketing areas, the better the performance of small and medium enterprises. The better the level of formal education, leadership, experience in business and the amount of motivation and skills in the performance of small and medium enterprises. The greater the desire for achievement, personal responsibility, management ability and innovation ability, the better the performance of small and medium enterprises. the higher the level of income of the community, the availability of jobs, a business climate and good investment and the better the economic growth, the better the performance of small and medium enterprises.